A techno-economic assessment of SNG production from agriculture residuals in China. Issue 5 (3rd May 2016) - Song, G.; Xiao, J.; Yu, Y.; Shen, L.
ABSTRACT: Biomass provides an attractive option for satisfying the demand of the rapid gas consumption growth. A process of BioSNG production via interconnected fluidized beds as gasification system and fluidized bed methanation reactor was modeled using Aspen Plus. The process performances and economic cost of BioSNG production from rice straw, wheat straw, corns stalk, and cotton straw were performed and compared. The exergy efficiency of BioSNG production from the four varieties of biomass ranges from 54.8% to 65.6%. With assumption on price of biomass including transportation of 250 RMB/t, the unit cost of BioSNG is equivalent to that of coal-based SNG. However, sensitivity analysis indicates that the unit cost of BioSNG linearly increases with the increase of biomass price. The exergy efficiency and unit cost results also strongly suggest that the CO2 produced during BioSNG production should be captured rather than treated as waste.